The sustainability of the types of floors used within the spaces of temporary housing in the Hajj season - Al-Hazmi, Najwa Nasser (Journal of Humanities & Social Sciences, 2022)
The current study aimed to identify the types of floors used in the spaces of temporary housing during the pilgrimage season to the holy places (Mina - Arafat - Muzdalifah) and the extent of their reflection on the guests of Rahman from the health side and to reveal the obstacles to the non-sustainability of the floors of the internal space with environmentally friendly materials, which has a positive impact on health environmental and functional. The study followed the descriptive analytical approach on the study sample (30 camps) for pilgrims’ companies (inside and outside) The study reached the following results: 1- There is a statistically significant correlation between the floors of the internal space of the temporary housing in the holy places and the health level of the pilgrims. 2- There is a statistically significant correlation between the non-sustainability of the floors of the internal space of the temporary housing with environment-friendly materials in the holy places and the economic aspect of the female pilgrimage partners, whether internal or external. 3- There is a positive and statistically significant correlation between the sustainability of the floors of the internal space of the temporary dwellings and the functional and aesthetic aspects of the temporary dwellings in the holy places. Among the most important recommendations of the study: 1- The study recommended opening the way for geologists, engineers, and those with expertise to study the nature of the Holy Land and use the best finishes to obtain sustainability and a healthy, sound environment. 2- Activating the role of the interior designer in creating an interior environment that meets the needs of the individual and society and achieves the aesthetic, functional and economical aspects of the interior spaces. 3- Advocating for a sustainable green interior design that does not harm the external environment but works to reduce its pollution.